2006
DOI: 10.1590/s1807-59322006000600011
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations in the Human Sinuatrial Nodal Artery

Abstract: Ortale JR, Paganoti C de F, Marchiori GF. Anatomical variations in the human sinuatrial nodal artery. Clinics. 2006;61(6): 551-8. OBJECTIVE:To analyze the anatomical variations of sinuatrial nodal branch(es) of the coronary artery mainly regarding their number; a recent report from Japan claims the presence of 2 branches in up to 50% of cases, an occurrence that would permit adequate flow compensation in case of occlusion or section of 1 of these branches. METHODS:The sinuatrial nodal branch(es) of 50 human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
21
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 15 publications
9
21
3
Order By: Relevance
“…In this sense low incidences in SNA's origin from RCA can be highlighted in the works of Ramanathan [32] in Indian population, Zangh [31] in Chinese, and Krupa [9] in Polish. Additionally, in our series we found a double SNA origin (3.4%), which is consistent with reports of Ramanathan [32] and Ortale [33] and slightly lower than…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this sense low incidences in SNA's origin from RCA can be highlighted in the works of Ramanathan [32] in Indian population, Zangh [31] in Chinese, and Krupa [9] in Polish. Additionally, in our series we found a double SNA origin (3.4%), which is consistent with reports of Ramanathan [32] and Ortale [33] and slightly lower than…”
Section: Discussionsupporting
confidence: 93%
“…The proximal caliber of SAN observed in this study is similar to the reported by Zangh et al [31], but slightly minor than others [8,14,30,33] reporting a caliper of 1.4-1.7 mm. These differences may be given by preparation and measuring methods, also in the height-weight people's characteristics.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Anatomical descriptions of the blood supply of the SNA have been reported previously, [3][4][5][6][7][8][9][10] but have been based solely on detailed cadaveric dissections and/or angiographic studies. However, it is difficult to dissect the SNA because of its tortuous course within the heart and although conventional CAG is the gold standard for clearly delineating the anatomical origin, course, and distribution of the SNA, it is an invasive technique associated with some complications and risks.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, our findings do not agree well with other studies in which the SNA predominantly originated from the RCA. [4][5][6][7][8][9][10] Berdajs et al found that 66% of the SNAs originated from the RCA, and 34% from the LCX. 4 Hadzeiselimovic et al found that 60% of the SNAs originated from the RCA and 40% from the LCX in 200 cadaveric hearts 5 and Bokeriya et al found 61.4% of the SNAs originated from the RCA and 38.4% from the LCX in 70 cadaveric hearts.…”
Section: Discussionmentioning
confidence: 99%